The Impact of Comprehensive Student Support on Crime: Evidence from the Pathways to Education Program - Adam Lavecchia; Philip Oreopoulos; Noah Spencer (CESifo GmbH, 2025)
This paper presents estimates of the causal effect of a comprehensive support program for low-income high school students on crime. The program, called Pathways to Education, bundles a number of supports including regular coaching, tutoring, group activities, free public transportation tickets and bursaries for postsecondary education. Our empirical strategy uses administrative data on high school enrollment linked to administrative court records and a difference-in-differences methodology that compares the evolution of crime outcomes of students living in the public housing communities where Pathways operates to similar public housing students who are ineligible for the program. We find that eligibility for Pathways reduces the likelihood of being charged with a crime at its Regent Park location by 6 percentage points (33 percent of the pre-treatment mean) and has no statistically significant effect at its Rexdale and Lawrence Heights locations. Our results suggest that the reductions in criminal activity are driven by the reduction of property crimes.
Keywords: I24; I26; I28; L31; 330; low-income youth; education and crime; youth programs